(untitled) (Revista Venezolana de Salud Pública, 2018)
Parasitic diseases affect millions of people worldwide, most commonly in children, are closely linked to poverty and other socio-economic factors. The study aimed to establish the relationship between intestinal parasites, and epidemiological and nutritional status in preschool educational institutions of the municipality Coropo, Aragua, Venezuela. We evaluated 145 children and their feces were analyzed using the techniques of physiological saline, Lugol, Kato, Faust, Baermann and Graham. Nutritional assessment was performed using clinical evaluation and anthropometric indicators, with the cut offs, excess: > p90; Normal: between p10 and p90; deficit: <p10. The frequency of intestinal parasites was 73.8% with predominance of protozoa (69.66%) on helminths (21.38%). The most frequent were: Blastocystis sp. (48.97%) and Enterobius vermicularis (20%). By linking epidemiological indicators with infected children, there was no significant association (p> 0.05). However, they observed a statistically significant association (p <0.05), washing hands before eating and after using the bathroom and the presence of intestinal parasites. We obtained a high percentage of normal in anthropometric indicators: Weight for the Age 80%, Size for Age 66.9%, Cephalic Circumference for the Age 71.72% and Brachial Circumference for the Age 82.76%, these can be influenced by the existence of a dining room where the children who study there have breakfast and lunch.. We conclude that despite the high rate of intestinal parasitic infections found, it did not affect the nutritional status of children tested